Gnathic Osteosarcoma: A Retrospective Analysis over a 20 Year Period - Prabhu, S; Jose, M; Iyengar, S (Kathmandu University Medical Journal, 2014)
Background Osteosarcomas are very rare malignant mesenchymal neoplasms affecting jaw bones. Only few studies are reported about this lesion in this particular region. Objective We wanted to assess the demography and tumor behaviour and histopathological pattern, retrospectively in the available cases. Methods A retrospective analysis of hospital records for 20 years was carried out. Clinical features, radiographic findings, histopathological details and treatment aspect of each of the lesions was considered. Results Findings of this study revealed only 13 cases of gnathic osteosarcomas, usually occurring in middle age, with equal sex predilection and predominantly seen in maxilla. Histopathologically, most of them belonged to osteogenic variant. Conclusion Only few cases of gnathic osteosarcomas are reported in this region mainly in the young males. Interestingly many of them has history of dental extraction before the onset of disease. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11024 Kathmandu University Medical Journal Vol.11(1) 2013: 37-40